Assistance with Product Branding for MSME Players - Fausta Ari Barata; Riyadi Nugroho (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Even though they now have very little management, MSME players in Bulakbentang Village, Kenjeran District, Surabaya, have a strong zeal for conducting their business. Among the issues at hand are low sales figures and a relatively narrow marketing reach. Due to the traditional methods of product promotion and the relatively plain nature of the product packaging, there is no compelling attraction for consumers. Business actors are still unaware of how crucial product packaging is to a marketing plan. As such, it is crucial to commit oneself to this community. MSME business actors in Bulakbentang Subdistrict have the option to select a service technique that involves counseling and packaging practices in order to address their existing issues. 36 MSME actors trained at the Bulakbentang Village Meeting Hall on September 30, 2023. After completing this program, each participant will have a better grasp of packaging, including the various materials that are used, how to choose the best packaging, and how to package their items in an eye-catching manner. As part of this service, you will receive instruction on digital product marketing and help with packaging.